Fungal Carbuncle due to Apophysomyces elegans – A Case Report - Samuel Dev Merlin; N. Bharath; K. R. Manoj Prabu; Khalilur Rahman; A. Rekha (Current Topics in Medicine and Medical Research Vol. 12, 2021)
Deep seated cutaneous fungal Infections are a rare entity in surgical practice and are very often under diagnosed. Presently they are also categorised as Type IV Necrotising Fasciitis. Aim: The aim of this paper is to sensitise clinicians to the nature and rapid lethality of deep seated fungal infections, and discuss the various methods at our disposal to deal with these peculiar cases. Discussion: Here we describe a deep seated cutaneous fungal infection in an immunocompetent patient and the challenges we faced during the course of his management. Due to the nature of presentation, atypical symptoms, co morbid conditions that cause immuno-compromise and slow but aggressive progression of the disease, the associated mortality is high. Conclusion: The onus is on the clinicians to diagnose a fungal etiology early and start appropriate anti fungal measures. A high index of suspicion, early aggressive rehabilitation and use of empirical antifungals, while cultures are awaited, may prove lifesaving in patients with a deep seated cutaneous fungal infection.